2019
DOI: 10.15252/msb.20199068
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic transcription in the p53‐mediated response to DNA damage is modulated by burst frequency

Abstract: Discontinuous transcription has been described for different mammalian cell lines and numerous promoters. However, our knowledge of how the activity of individual promoters is adjusted by dynamic signaling inputs from transcription factors is limited. To address this question, we characterized the activity of selected target genes that are regulated by pulsatile accumulation of the tumor suppressor p53 in response to ionizing radiation. We performed time‐resolved measurements of gene expression at the single‐c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 113 publications
(166 reference statements)
2
24
0
Order By: Relevance
“…We observed similar activation strengths varying from about 1.5 fold change in GFP fluorescence to 4 fold change, with slight increases upon doubling the amount of TF transfected. Such fold change up-regulation is in the range of physiological induction in mammalian signalling pathways (Strasen et al, 2018;Wong et al, 2019;Friedrich et al, 2019). A similar dose-dependent increase in reporter signal is also observed at the mRNA level ( Fig.…”
Section: Observation Of Kinetic Synergy Using a Synthetic Platformsupporting
confidence: 74%
“…We observed similar activation strengths varying from about 1.5 fold change in GFP fluorescence to 4 fold change, with slight increases upon doubling the amount of TF transfected. Such fold change up-regulation is in the range of physiological induction in mammalian signalling pathways (Strasen et al, 2018;Wong et al, 2019;Friedrich et al, 2019). A similar dose-dependent increase in reporter signal is also observed at the mRNA level ( Fig.…”
Section: Observation Of Kinetic Synergy Using a Synthetic Platformsupporting
confidence: 74%
“…Increases in burst frequency in response to transcription factor stimulation have been more commonly observed than increases in burst size (Chen et al, 2019;Friedrich et al, 2019;Li et al, 2018). Notably, most of these examples analyzed cellular processes for which it is important that most or all cells in a population respond to a stimulus with similar levels of gene expression such as the DNA damage response (Friedrich et al, 2019) or the circadian response to light (Li et al, 2018). In contrast, for processes where highly skewed single-cell responses are beneficial, as appears to be the case for inflammatory signaling, stimulus-induced burst size increases may be more common.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of a range of transcription factors (TFs) has been associated with changes in burst frequency for many genes (Chen et al, 2019;Friedrich et al, 2019;Li et al, 2018), but TFmediated changes in burst size have not been as widely reported. To search for potential differences in molecular events linked to changes in burst size after TNF treatment, we measured chromatin features and binding of transcriptional machinery at our target promoters using ChIP.…”
Section: Tnf-mediated Increases In Burst Size Are Associated With Rnamentioning
confidence: 99%
“…These and other single cell studies revealed that the combinations of expressed genes are not uniform in a cell population but are subject to substantial variations, in part due to the inherently stochastic nature of RNA synthesis and degradation (2)(3)(4). Notwithstanding this variability, specific combinatorial patterns have been identified, among which the stochastic exclusive gene expression of the odorant and T-cell receptors has received a widespread attention.…”
Section: Introductionmentioning
confidence: 99%
“…2 One cell from this dataset was excluded from the analysis since it showed no expression for the whole gene set. 3 There are three types of mice crossing: 1) C57BL/6J (C57) female mice mated to C57 male mice; 2) CAST/EiJ (CAST) female mice mated to C57 male mice; 3) C57 female mice mated to CAST male mice. 4 The analysed data comprise blood endothelial cells and high endothelial cells.…”
mentioning
confidence: 99%